Questioning Market Orthodoxy: Perceptions of Chinese State-Capitalism in Ghana - Daniel Abankwa (Cogent Social Sciences)
The discourse surrounding China’s state-capitalist economic model has garnered attention among scholars and practitioners, who have noted its growing appeal in developing nations. This model, which blends elements of state control with market-driven forces, was prominently showcased during the 19th National Congress of the Chinese Communist Party in 2017, where Xi Jinping lauded it as a pioneering approach to modernization. Despite skepticism regarding its universal applicability, this study investigates how Ghanaian elites perceive state capitalism and its potential applicability in Ghana. The findings reveal a prevalent pattern among respondents expressing disillusionment with traditional capitalist structures and demonstrating openness to exploring China’s state-capitalist model as an alternative pathway to development. While some respondents emphasized the importance of developing a distinct, nationally tailored economic system that incorporates elements of the Chinese approach, most saw value in adopting key aspects of state capitalism. Intriguingly, the study reveals circumstances where, despite some Ghanaian elites expressing concerns about the shortcomings of free market capitalism, they tend to support neoliberal principles overall.